Pengaruh Customer Review, Flash Sale Promotion Dan Live Streaming Terhadap Keputusan Pembelian Pada E-Commerce Shopee Di Surakarta - Fatmala, Keke Ferary Anjani; Pamikatsih, Tri Ratna (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research was conducted with the aim of finding out the influence of customer reviews, flash sale promotions and live streaming on purchasing decisions on Shopee e-commerce. Surakarta was the population in this study with the method used, namely the pur-posive sampling method so that the number of respondents in this study was 130 respondents. The data collection technique used in this research is a quantitative method by distributing questionnaires online via social media. Multiple regression is the analysis method used in this research. This research partially shows that customer reviews, flash sale promotions and live streaming have a positive and significant effect on purchasing decisions on Shopee e-commerce.